2021
DOI: 10.1037/pspi0000333
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the system constructively: Testing the effectiveness of nonnormative nonviolent collective action.

Abstract: Collective action research tends to focus on motivations of the disadvantaged group, rather than on which tactics are effective at driving the advantaged group to make concessions to the disadvantaged. We focused on the potential of nonnormative nonviolent action as a tactic to generate support for concessions among advantaged group members who are resistant to social change. We propose that this tactic, relative to normative nonviolent and to violent action, is particularly effective because it reflects const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 74 publications
(157 reference statements)
3
52
0
1
Order By: Relevance
“…Based on these two measures, we calculated a score representing indirect shared ownership perceptions using a formula developed in the literature on dual identity and constructive disruption (see Shuman, Saguy, van Zomeren, & Halperin, 2020). Our adapted formula is: ðingroup ownership þ outgroup ownershipÞ À jingroup ownership À outgroup ownershipj By subtracting the absolute value of the difference between ingroup and outgroup ownership perceptions from the sum of the two, this formula allocates higher values to participants who strongly agreed with both ingroup and outgroup ownership (shared ownership perceptions, e.g., (7 + 7) − |7 − 7| = 14 -0 = 14), but lower values to participants who either agreed with no group ownership (e.g., (1 + 1) − | 1 − 1| = 2 -0 = 2), or only with one of the two (ingroup ownership perceptions, e.g., (7 + 1) − |7 − 1| = 8 − 6 = 2, or outgroup ownership perceptions, e.g., (1 + 7) − | 1 − 7| = 8 − 6 = 2).…”
Section: Methodsmentioning
confidence: 99%
“…Based on these two measures, we calculated a score representing indirect shared ownership perceptions using a formula developed in the literature on dual identity and constructive disruption (see Shuman, Saguy, van Zomeren, & Halperin, 2020). Our adapted formula is: ðingroup ownership þ outgroup ownershipÞ À jingroup ownership À outgroup ownershipj By subtracting the absolute value of the difference between ingroup and outgroup ownership perceptions from the sum of the two, this formula allocates higher values to participants who strongly agreed with both ingroup and outgroup ownership (shared ownership perceptions, e.g., (7 + 7) − |7 − 7| = 14 -0 = 14), but lower values to participants who either agreed with no group ownership (e.g., (1 + 1) − | 1 − 1| = 2 -0 = 2), or only with one of the two (ingroup ownership perceptions, e.g., (7 + 1) − |7 − 1| = 8 − 6 = 2, or outgroup ownership perceptions, e.g., (1 + 7) − | 1 − 7| = 8 − 6 = 2).…”
Section: Methodsmentioning
confidence: 99%
“…We aimed to provide experimental evidence for our main hypotheses: first, that a strong perceived moral violation would trigger increased support for collective action (the moral violation hypothesis), and second, that this increased support would apply to all forms of collective action (the ends justify the means hypothesis). To test our ends justify the means hypothesis more fully, we examined support for three types of collective action: nonviolent normative action, referring to any action that is within socially accepted and legal norms of society (hereafter referred to as normative action), nonviolent nonnormative action, referring to forms of action that are not societally normative but also not violent (hereafter nonnormative action; see Shuman et al., 2020), and violent nonnormative action, referring to action that is not societally nonnormative and violent (hereafter violent action; see Tausch et al., 2011). According to the ends justify the means hypothesis, a perceived moral violation should increase willingness to engage in all three types of action.…”
Section: Studymentioning
confidence: 99%
“…Many of the studies showing that nonviolence is more effective focus on more attitudinal outcomes such as identification with the protestors, attitudinal support, and mobilization in support of the movement. 10,37,38 Whereas, many of the studies that have found positive effects of violence have used more policy related outcomes [5][6][7][8]25 . Thus, it may be that different types of protest are effective for different goals.…”
Section: Discussionmentioning
confidence: 99%
“…Based on sociological and social-psychological theorizing and research 13,[23][24][25] , disruptive protests may be able to generate support for making the policy changes demanded by the movement. Indeed, some theories on large scale mass protests argue that they derive their power from the ability to disrupt normally cooperative relations and the broader social order.…”
Section: Effectiveness Of Protests In Terms Of Policy Support or Prejudice?mentioning
confidence: 99%
See 1 more Smart Citation